AnAlysis of The effecT of fiscAl sTimulus Policy of infrAsTrucTure To The economy of indonesiA (sociAl AccounTing mATrix APProAch) - Hendro Ratnanto (Widyariset, 2011)
The focus of this research is to determine the effect of fiscal stimulus policy of infrastructure to the economyof Indonesia. Research method used is Social Accounting Matrix (SAM). The simulation result indicates that fiscalstimulus policy of infrastructure has a positive effect to the revenue growth of production factors, households,and production activities. Fiscal stimulus also affect the growth of other sectors outside the infrastructure sector,including mining and quarrying, forestry, and timber industry. Based on a structural path analysis it can beconcluded that the global effect of the infrastructure sector to household is carried out through the productionfactors labour and capital.